2015
DOI: 10.1186/s12929-015-0125-3
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidinyl caffeamide against ischemia/reperfusion injury in cardiomyocytes through AMPK/AKT pathways

Abstract: BackgroundCoronary heart disease is a leading cause of death in the world and therapy to reduce injury is still needed. The uncoupling of glycolysis and glucose oxidation induces lactate accumulation during myocardial ischemia/reperfusion (I/R) injury. Cell death occurs and finally leads to myocardial infarction. Caffeic acid, one of the major phenolic constituents in nature, acts as an antioxidant. Pyrrolidinyl caffeamide (PLCA), a new derivative of caffeic acid, was synthesized by our team. We aimed to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…However, when oxygen supply limits (during myocardial ischemic event), a shift in the myocardial metabolism from fatty acid to glucose is initiated as it is more oxygen efficient and prevents deleterious effects. Previously, activation of AMPK/AKT signaling has also been demonstrated to enhance myocardial glucose uptake thus alleviating MI/R injury [ 54 , 55 ]. So, the effect of diallyl trisulfide on glucose utilization during MI/R injury deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…However, when oxygen supply limits (during myocardial ischemic event), a shift in the myocardial metabolism from fatty acid to glucose is initiated as it is more oxygen efficient and prevents deleterious effects. Previously, activation of AMPK/AKT signaling has also been demonstrated to enhance myocardial glucose uptake thus alleviating MI/R injury [ 54 , 55 ]. So, the effect of diallyl trisulfide on glucose utilization during MI/R injury deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence indicated that AMPK/AKT pathway is involved in cardiac protection 21 , 22 . A mechanistic study showed that FGF21-induced antiapoptotic effect in T1DM mice is attributed to the activation of AMP-activated protein kinase (AMPK) followed by inactivation of phosphatase and tensin homolog (PTEN) that negatively regulates AKT signaling 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that AMPK, a major cellular sensor of energy availability, is involved in the progression of cardiac injury caused by different factors [32][33][34]. To explore whether AMPK is involved in FGF21 against diabetes-induced cardiac injury, we first evaluated AMPK activity in FGF21 KO and WT mice.…”
Section: Fgf21 Alleviates Hg-induced Oxidative Stress and Fibrosis Bymentioning
confidence: 99%